UMP–MARA collaboration pioneers Halal Gelatin Project - Mimi Rabita, Abdul Wahit (2020)
Kuala Lumpur, 30 September 2020 - The country’s first halal gelatin project will begin in Pahang soon when Universiti Malaysia Pahang (UMP) received the remaining RM5 million via the collaboration project with the Majlis Amanah Rakyat (MARA) involving a total allocation of RM20 million which is disbursed in stages in the form of grants.